Analisis Penggunaan Aplikasi Schoology Terhadap Minat Belajar Siswa Kelas XI IPS MA Nurul Jadid Sumber Anyar - Hasanah, Kholifatul; Jaya, Firman; Yuliana, Dyan (Journal of Science and Education Research, 2023)
This study aims to determine the use of the schoology application on the interest in learning of class XI social studies students. Approach This research uses a qualitative descriptive approach. Respondents in this study were 2 IT (Information Technology) teachers and five students of class XI IPS MA Nurul Jadid from 18 students. Data collection techniques carried out include observation and interviews. Data analysis techniques in this study include data reduction, data presentation, and drawing conclusions. Based on the results of the research and discussion, it can be concluded that the use of the Schoology application can be carried out well in class XI IPS MA Nurul Jadid Sumber Anyar. Analysis of the use of the Schoology application by focusing on student interest in independent character, discipline and responsibility.